A Pediatric Case of IgA Nephropathy Associated with Familial Mediterranean Fever - Chbihi, Marwa; Dumaine, Cécile; Deschênes, Georges; Couderc, Anne; Monteiro, Renato C; Hogan, Julien; Cambier, Alexandra (Archives of Clinical and Medical Case Reports, 2020)
IgA nephropathy (IgAN) is one of the most common primary glomerulonephritis in children and adolescents. Pharyngitis infections are known to be a trigger of IgA attacks. It has been suggested that IgAN is an immune complex disease with circulating immune complexes galactose-deficient IgA1 (Gd-IgA1), IgG and IgA anti-Gd-IgA1 antibodies, and soluble CD89. Amyloidosis is the most common renal complication of Familial Mediterranean Fever (FMF), the most common form of auto-inflammatory syndromes characterized by flares of fever and polyserositis. Besides amyloidosis, other renal lesions have been exceptionally reported in patients with FMF and other hereditary periodic fevers. We report a child who presented with haematuria during febrile attacks in the context of FMF, and in whom kidney biopsy revealed deposits of predominant mesangial IgA with no evidence of amyloidosis and presence of immune complexes in the serum (Gd-IgA and sCD89-IgA).